Analysis of Interpersonal Communication Patterns of Love Scams Mode on Social Media in Female Students in Medan City - Syecha; Sumanti, Solihah Titin (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
One of the modes that takes the most victims, especially women, is love scams. This mode is to find a mate in cyberspace. People who don't have a soul mate or who are lonely try to find a partner through the internet. The purpose of this study was to determine the pattern of interpersonal communication mode love scams on social media in UIN North Sumatra students. This research covers various issues such as the formulation of the problem, namely, how the mode of love scams on social media among female students can occur. To answer these problems thoroughly and deeply. The research method used is qualitative content analysis using Computer Mediated Communication (CMC) Models consisting of impersonal, interpersonal and hyperpersonal. The study concluded that all three patterns are established in love scam cases. Analysis of this study will be conducted interviews with several sources and observations which will then be verified so that the research is relevant. The results of this study show that often interpersonal communication carried out via social media can create self-disclosure (self-disclosure) which creates high trust between one party which can lead to the occurrence of love scammers. Research contributions based on technological developments that continue to grow and become more sophisticated will also bring greater dangers, one of which is cyber crime, although the number of cases of cybercrime victims is very high, but only a few people dare to report. This is due to the lack of a supervisory system and law in our country, therefore users are required to be good at maintaining personal privacy to avoid crime on social media.